Pengolahan Limbah dan Pencemaran Lingkungan Tahun 2010–2018 - Mardhiyah, Antis Sholihatul; Krisnadi, IG (Historia, 2022)
This study discusses the waste treatment by PT.Putra Restu Ibu Abadi (PT.PRIA) and environmental pollution in Lakardowo Village, Jetis District, Mojokerto regency in 2010-2018. The problem to be dealt with here are: the presence of the factory B3 waste treatment as a solution to waste problems from the growing development industry in East Java, the process of establishment and development of PT. PRIA, the influences of the establishment PT. PRIA on socio-economic and environmental conditions, as well as conflicts that arise as a result of the influence of the PT. PRIA. The research used a historical method according to Louis Gottschalk which includes four stages, namely the stages of heuristics, criticism, interpretation and historiography. In analyzing the problem of what happened in Lakardowo Village, the study used an environmental sociology approach from Rachmad K.Dwi Susilo and Giddens' social movement theory. Environmental pollution had an impact on the decline in the environmental quality of Lakardowo Village, thus affecting the social and economic conditions of the people. This situation raised a protest from the community, the response from PT. PRIA, and the government was present as a mediator from problems that occured in Lakardowo Village.